Going Concern Bisnis Berdasarkan Perspektif Maqashid Syari’ah (Studi Di PT. Lentera Jaya Madina) - Rozi, Danu; Riduwan, Akhmad; Fidiana, Fidiana (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze business sustainability (going concern) in dealing with organizational problems from a maqashid sharia perspective. The object of this research is PT. Lentera Jaya Madina in Surabaya City. This research uses a qualitative approach. The data collection process was carried out through in-depth interviews, observation and document study. Interviews were conducted with several informants. Document studies were carried out to see evidence of continuous improvements made by management in financial reports, observations were made on the implementation of sustainability programs in the company. The analysis results show that PT. Lentera Jaya Madina has overhauled regulations and culture and produced 10 values ​​as a form of organizational sustainability. Based on Hifdzud Din's perspective, it is contained in the amaliyah value of worship which is implemented through the obligation to pray in congregation, regular recitation of the Koran and recitation of the Qur'an. Hifdzul Aql is contained in the value of integrity which is implemented by increasing employee capacity. Hifdzun Nasl contained in the synergy value which is implemented by implementing the program family gathering and assistance in finding a soul mate. Hifdzun Nafs contained in the values ​​of responsibility and Akhlaqul Karimah. Hifdzul Mal is contained in the values ​​of compensation, trustworthiness, honesty, morality, service and integrity.